On the Accuracy of Vertical Deflection Measurements Using the High-Precision Digital Zenith Camera System TZK2-D - Hirt, Christian; Reese, B.; Enslin, H. (Springer, 2004)
In this paper the accuracy of vertical deflections provided by the Digital Zenith Camera System TZK2-D is comprehensively analysed. During 2003 and 2004 various vertical deflections have been measured repeatedly at particular sites with different types of comparative data available. Emphasis is placed on the presentation of comparative measurements with highly accurate reference data at the Hamburg PZT station. As main result, the external accuracy level of the deflection data has been found to be about 0".10 - 0".15 as such exceeding considerably the accuracy of the formerly used photographic zenith cameras. The high accuracy level makes the Digital Zenith Camera System TZK2-D a very powerful system for highly accurate geoid determination in local areas.